Numerical prediction of statistical masonry wall fragment distribution induced by blast loading - Wang, M.; Hao, Hong; Ding, Y.; Li, Z. (Tianjin Daxue/Tianjin University, 2008)
The hazard caused by the fragments of damaged structures is usually significant in accidental explosions or hostile blast events. A reliable and efficient method to estimate probable fragment size, velocity and launch distance will be useful to assess and design countermeasures to mitigate the possible fragment hazards. This paper presents a numerical method for predicting the size and launch distance of the fragments caused by explosive damage of masonry wall. Numerical simulations with different scaled distances are carried out, and the statistical distribution functions of the fragment size and launch distance in terms of the scaled distance are derived.